Cardiorehabilitation аnd quality of life of patients with cardiovascular diseases - T. A. Evdokimova; A. E. Kutuzova; A. A. Potapchuk; O. E. Malneva (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Submitted data detected miscellaneous changes of life quality indicators of patients with cardiovascular pathology who took part in cardiorehabilitation programmes of various duration. Рatientsinvolved in programme of shortterm (inpatient) walking sessions showed improvement of tolerance of stress test, anxiety decrease, quality of life (physical and social functioning, vitality) improvement. Quality of life improvement is correlated to increase in figures of final exercise tolerance test. Body mass index, waist circumference size, state anxiety reduced in patients who took part in 6month aerobic treadmill and aquatraining programme. Regardless of the fact that changes in tolerance of exercise tolerance test were not detected, patients’ quality of life as well as their physical functioning and vitality increased. Patients also saw improvements in emotional and social functioning, general health.